Rules for Investigating Cost Variances - Duvall, Richard M. (Management Science, 1967)
Several writers have suggested quality control procedures in order to determine when an observed variance of actual cost from standard cost should be investigated in order to determine if the variance is due to non-standard performance. These procedures do not explicitly consider the cost of an investigation and the benefits derived from discovering and correcting the cause for the variance. The purpose of this paper is to indicate how these costs may be made a part of the decision to investigate a given cost variance.